2021
DOI: 10.1039/d1sm01191j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphology and particle–wall interaction on colloidal near-wall dynamics

Abstract: We investigated the near-wall Brownian dynamics of different types of colloidal particles with a typical size in the 100 nm range using evanescent wave dynamic light scattering (EWDLS). In detail...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…More symmetric shapes require fewer coefficients 2,3 , down to the case of sphere-like objects, whose motion is fully described by one translational and one rotational drag coefficient, directly connected to the particle's translational and rotational diffusivity, D T and D R , via simple Stokes-Einstein relations. However, even for colloidal spheres, symmetry in the dynamics may be broken by interactions with confining walls [4][5][6] . In addition to stochastic diffusive motion, particles can also be made to translate or rotate deterministically along prescribed directions in the presa Laboratory for Soft Materials and Interfaces, Department of Materials, ETH Zurich, CH-8093, Zurich, Switzerland; E-mail: lucio.isa@mat.ethz.ch † Electronic Supplementary Information (ESI) available: Additional details of experimental procedures and report of additional syntheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More symmetric shapes require fewer coefficients 2,3 , down to the case of sphere-like objects, whose motion is fully described by one translational and one rotational drag coefficient, directly connected to the particle's translational and rotational diffusivity, D T and D R , via simple Stokes-Einstein relations. However, even for colloidal spheres, symmetry in the dynamics may be broken by interactions with confining walls [4][5][6] . In addition to stochastic diffusive motion, particles can also be made to translate or rotate deterministically along prescribed directions in the presa Laboratory for Soft Materials and Interfaces, Department of Materials, ETH Zurich, CH-8093, Zurich, Switzerland; E-mail: lucio.isa@mat.ethz.ch † Electronic Supplementary Information (ESI) available: Additional details of experimental procedures and report of additional syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…However, even for colloidal spheres, symmetry in the dynamics may be broken by interactions with confining walls. [4][5][6] In addition to stochastic diffusive motion, particles can also be made to translate or rotate deterministically along prescribed directions in the presence of external fields, such as flow, magnetic or electric fields, thus also requiring the determination of three translational and three angular velocities. Finally, any combination of diffusive and deterministic motion is possible, such as in the case of active Brownian motion, where a particle has a selfgenerated constant propulsion velocity, whose direction is randomised by rotational diffusion, and which is superimposed to translational random displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the principles of EWDLS can refer to several previous works. 45–47 Based on EWDLS, researchers have been able to accomplish more studies about near-interface dynamics in recent decades, including the measurements with nanoparticles, the measurements of the translational and rotational diffusion of spherical colloids, and the influence of surface morphology on near-interface diffusion. 45–47…”
Section: Typical Near-interface Interactions and Dynamics Measured Wi...mentioning
confidence: 99%
“…5F). 46 Standard silica spheres with a smooth surface (SSi), silica spheres with controlled surface roughness (Rsi), as well as microporous silica hollow shells (his) were employed in the EWDLS measurements. Compared to the other two types of particles, the authors found that the RSi particles did not adsorb at the glass–water interface.…”
Section: Advances In Tirm Measurementsmentioning
confidence: 99%
See 1 more Smart Citation